A multi-nozzle nebuliser does not improve tissue drug delivery during PIPAC - Sautkin, Yaroslaw; Weinreich, Juergen; Reymond, Marc André (Surgical endoscopy, 2024)
Background Multi-nozzle nebulisers for pressurised intraperitoneal aerosol chemotherapy (PIPAC) are implemented in clinical practice to improve the homogeneity of tissue drug delivery. Nonetheless, the advantages of such devices over one-nozzle nebulisers have not been demonstrated thus far. In this study, we compared the performance of multi- and one-nozzle nebulisers by conducting physical and ex vivo pharmacological experiments. Methods The one-nozzle nebuliser Capnopen® and the multi-nozzle nebuliser were the subjects of this study. In physical experiments, the aerosol droplet size was measured by laser diffraction spectroscopy. Spatial spray patterns were depicted on blotting paper. Pharmacological experiments were performed on the enhanced inverted bovine urinary bladder model, demonstrating real-time tissue drug delivery, aerosol sedimentation and homogeneity of doxorubicin and cisplatin tissue distribution. Results The multi-nozzle nebuliser had a sixfold greater aerosolisation flow and a threefold greater angle of aerosolisation than Capnopen®. The aerosol particle size and distribution range were higher than that of Capnopen®. Spray patterns on blotting paper were more extensive with the multi-nozzle nebuliser. Real-time tissue drug delivery with the multi-nozzle nebuliser was over 100 ml within 1 min, and the aerosol sedimentation was 48.9% ± 21.2%, which was not significantly different from that of Capnopen®. The doxorubicin and cisplatin tissue concentrations were greater with Capnopen®. Although there was no significant difference in the homogeneity of doxorubicin distribution between the two devices, the homogeneity of cisplatin distribution was significantly higher with Capnopen®. Conclusion The multi-nozzle PIPAC nebuliser did not fulfil expectations. Even though the surface spray patterns were broader with the multi-nozzle nebuliser, the tissue drug homogeneity and concentration were greater with Capnopen®. Graphical Abstract